2011
DOI: 10.4067/s0717-97072011000400006
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Antihypertensive Activity of Some New Substituted Pyridazine Derivatives

Abstract: Some new 6-(substituted phenyl)-2-(4-substituted phenyl-5-thioxo-4,5-dihydro-1H-1,2,4-triazol-3-yl)-4,5-dihydropyridazin-3(2H)-one derivatives were synthesized by a sequence of reactions starting from respective aryl hydrocarbons. The final compounds (4a-i) were screened for antihypertensive activities by non-invasive method using Tail Cuff method. The compounds 4e and 4i showed appreciable antihypertensive activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…In this work, an antihypertensive agent 2-(2,6-dichlororbenzylidenehydrazino)-1,4,5,6-tetrahydropyrimidine hydrochloride ( 3 ) (OT-24) was synthesized as the anti-isomer ( E -isomer) by the experimentation of the nuclear Overhauser effect (NOE) and, by a process of irradiation with ultraviolet light in an aqueous or methanolic solution, it was instantly converted to its syn-isomer ( Z -isomer). Not long ago, the compound ( Z )-2-(2-(2,6-dichlorobenzylidene)hydrazinyl)pyrimidine ( 4 ) and its related 2-benzylidenehydrazinopyrimidine derivatives exhibited remarkable antibacterial activity as shown below in Figure 3 [ 63 ].…”
Section: Applications Of Heterocyclic Compoundsmentioning
confidence: 99%
“…In this work, an antihypertensive agent 2-(2,6-dichlororbenzylidenehydrazino)-1,4,5,6-tetrahydropyrimidine hydrochloride ( 3 ) (OT-24) was synthesized as the anti-isomer ( E -isomer) by the experimentation of the nuclear Overhauser effect (NOE) and, by a process of irradiation with ultraviolet light in an aqueous or methanolic solution, it was instantly converted to its syn-isomer ( Z -isomer). Not long ago, the compound ( Z )-2-(2-(2,6-dichlorobenzylidene)hydrazinyl)pyrimidine ( 4 ) and its related 2-benzylidenehydrazinopyrimidine derivatives exhibited remarkable antibacterial activity as shown below in Figure 3 [ 63 ].…”
Section: Applications Of Heterocyclic Compoundsmentioning
confidence: 99%
“…Each rat was placed in restrainer and appropriate cuff with sensor was mounted on its tail and warmed to about 33-35 ° C. The tail cuff was inflated to a pressure above 200 mmHg, systolic blood pressure; diastolic blood pressure and heart rate were measured directly by the tail cuff and pulse sensor. 15…”
Section: Hypotensive Activity In Normotensive Ratsmentioning
confidence: 99%
“…From this research study, authors concluded that incorporation of amino and carboxylic acid groups into the structure of pyridazinone derivatives can enhance the ACE inhibitory activity of this class of compounds. Moreover, R. Mishra et al, [38] introduced a series of 4,5-dihydro-1H-(1,2,4-triazol-3-yl)-4,5-dihydropyridazin-3(2H)-one derivatives and evaluated their antihypertensive activity using Tail Cuff method. This study revealed that compounds 34 and 35 reduced the mean arterial blood pressure (MABP) by (41.84 and 40.98%), respectively in comparable results to the standard drugs propranolol and hydralazine (41.40 and 41.76%), respectively.…”
Section: Antihypertensive Activitymentioning
confidence: 99%